First Report of Diaporthe eres associated with stem and branch canker on Quercus robur in Croatia (Journal of Forestry, 2025)
In June 2020, stem and branch cankers were observed on young Quercus robur trees growing in a floodplain forest near the Sava River in the eastern part of Croatia. Samples of affected stems and branches were randomly collected, and fungi present in the symptomatic tissue were isolated on agar media. The molecular and morphological identification of the obtained cultures revealed 29 fungal isolates belonging to 12 different taxa. The most frequently isolated species was Diaporthe eres, found in 77% of sampled trees. The ability of D. eres to cause cankers was tested in a pathogenicity trial on 3-year-old Q. robur saplings. Bark and wood necroses developed on all inoculated saplings, and D. eres was successfully re-isolated and identified using molecular tools. None of the control saplings revealed any symptoms during the trial. Therefore, Koch’s postulates were fulfilled, and D. eres was verified as a causative agent of cankers on Q. robur.